Reorienting Jamāluddīn ‘Aṭiyyah’s Maqāṣid al-Usrah in the Regulation of Polygamy in the Indonesian Compilation of Islamic Law - Musadad, Ahmad; Choiri, Muttaqin; Qomaro, Galuh Widitya; Fauzi, Alfa Zaidanil; Imamuddin, Imamuddin; Pujiati, Tri (Sakina: Journal of Family Studies, 2025)
This article discusses the reconstruction and reorientation of polygamy regulations in the Compilation of Islamic Law (KHI), specifically Articles 55–59, through the philosophical framework of maqāṣid al-usrah developed by Jamāluddīn ‘Aṭiyyah. This research is crucial given that the KHI, having been in force for over 30 years, requires a new reading (the expedient of re-interpretation) to preserve the values of maqāṣid in facing contemporary social dynamics. This qualitative study, utilizing a library research method and content analysis, aims to explore the maqāṣid values and evaluate their alignment with Indonesia’s positive legal norms. The analysis results indicate that the KHI implicitly integrates three core dimensions of ‘Aṭiyyah’s maqāṣid al-usrah, namely taḥqīq al-sakīnah wa al-mawaddah wa al-raḥmah, tanẓīm al-’alāqah bayn al-jinsayn, and tanẓīm al-jānib al-mālī li al-usrah, primarily through the key requirement of acting justly (Article 55 Paragraph 2) and the necessity of obtaining permission from the Religious Court (Article 56). ‘Aṭiyyah’s concept, which demands psychological and emotional justice (al-’adālah al-nāfsi-yah wa al-wijdāni-yah), provides a strong foundation for reorienting the interpretation, shifting the focus from formal procedure to the substance of the objective. The article recommends adding ethical and social clauses (such as psychological assessment) and explicitly integrating the maqāṣid al-usrah principles into the KHI, so that Islamic family law can serve as a contextual, humanistic, and solution-oriented guide in realizing substantive justice and protecting family sakīnah.